2019
DOI: 10.1002/smll.201901544
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Photodiode Based on Atomically Thin WSe2/MoS2 Nanoscroll Integration

Abstract: Self‐assembled structures of 2D materials with novel physical and chemical properties, such as the good electrical and optoelectrical performance in nanoscrolls, have attracted a lot of attention. However, high photoresponse speed as well as high responsivity cannot be achieved simultaneously in the nanoscrolls. Here, a photodiode consisting of single MoS2 nanoscrolls and a p‐type WSe2 is demonstrated and shows excellent photovoltaic characteristics with a large open‐circuit voltage of 0.18 V and high current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 54 publications
(69 reference statements)
3
34
1
Order By: Relevance
“…On the other hand, we calculated the important indicators of photovoltaic energy conversion: fill factor (FF) and external quantum efficiency (EQE) for our WSe 2 /Bi 2 O 2 Se self‐driven detector by the formula: FF = P el,max /( I sc V oc ) and EQE = ( I ph / P )( hc / qλ ) = R ( hc / qλ ) (where h is the Planck constant, q is the unit charge and λ is the excitation wavelength). [ 41,60 ] From the Figure 5e, the WSe 2 /Bi 2 O 2 Se heterostructure obtained maximum FF of 0.24 and EQE up to 66.27% under 52.27 and 1.12 mW cm −2 , respectively, which is comparable to reported values based on MoS 2 /WSe 2 (1.5%, 34%), [ 47,59 ] MoS 2 /BP (0.3%) [ 41 ] and AsP/InSe (1.5%). [ 42 ] The power conversion efficiency defined as η PV = P el / P in was calculated ≈ 0.428% under 52.27 mW cm −2 .…”
Section: Resultssupporting
confidence: 78%
“…On the other hand, we calculated the important indicators of photovoltaic energy conversion: fill factor (FF) and external quantum efficiency (EQE) for our WSe 2 /Bi 2 O 2 Se self‐driven detector by the formula: FF = P el,max /( I sc V oc ) and EQE = ( I ph / P )( hc / qλ ) = R ( hc / qλ ) (where h is the Planck constant, q is the unit charge and λ is the excitation wavelength). [ 41,60 ] From the Figure 5e, the WSe 2 /Bi 2 O 2 Se heterostructure obtained maximum FF of 0.24 and EQE up to 66.27% under 52.27 and 1.12 mW cm −2 , respectively, which is comparable to reported values based on MoS 2 /WSe 2 (1.5%, 34%), [ 47,59 ] MoS 2 /BP (0.3%) [ 41 ] and AsP/InSe (1.5%). [ 42 ] The power conversion efficiency defined as η PV = P el / P in was calculated ≈ 0.428% under 52.27 mW cm −2 .…”
Section: Resultssupporting
confidence: 78%
“…[52][53][54] Based on the above equation, the average R values were calculated to be 63.57 and 131.02 µA/W for the 1 and 4 nm samples, respectively. The results also show that the photo-responsivity does not degrade with increasing illumination intensity, unlike the previous observations with 2D MoS2 layers prepared on other planar substrates, [55][56][57][58][59] indicating that these 2D MoS2 layers/TOCN composites maintain excellent structural integrity (See Fig. S4, ESI †).…”
Section: Please Do Not Adjust Marginscontrasting
confidence: 41%
“…This study showed low-power consumption MoS 2 nanoscroll-based photodetections where avalanche multiplication effect enhanced the photoresponsivity in MoS 2 nanoscrolls compared with atomically thin monolayer MoS 2 . Deng et al 381 reported photodiodes having p-type WSe 2 and single MoS 2 nanoscrolls which showed suppressed dark current and two orders of magnitude increase in the ratio of photocurrent to dark current compared with a single MoS 2 nanoscroll-based photodiode. Fig.…”
Section: Mos 2 Nanoscrollsmentioning
confidence: 99%